Establishing Sustainable Education for Fashion and Textiledesign According to the SDG - Chen Li; Apisak Sindhuphak (My University, 2024)
Objective: This study aimed to integrate Sustainable Development Goals (SDGs) into fashion and textile industry education. It sought to connect the supply chain and address the growing demand for sustainability in the industry through interdisciplinary solutions. Theoretical Framework: Several key theoretical concepts and models were grounded. The SDGs provided a broad framework for integrating environmental, ethical, and social considerations into industry practices. The Triple Bottom Line (TBL) theory was used to understand how economic, environmental, and social dimensions could be balanced in the fashion and textile industry. Additionally, Stakeholder Theory was employed to analyze the interactions between academic institutions and industry supply chains. Method: A qualitative analysis was employed, focusing on how sustainable development was practiced in architectural education. Industry professionals were interviewed to understand industry experiences and needs. A literature review method was used to systematically collect, assess, and synthesize existing research findings. Results and Discussion: The results obtained revealed that fashion and textile colleges needed to establish teaching methods guided by the SDGs. Both academic and supply chain responses were positive, highlighting the potential and feasibility of this teaching model. Research Implications: The practical and theoretical significance of this study was discussed, providing insights into how the research findings could be applied or impact sustainable teaching models. These implications could endow designers with necessary sustainability knowledge, skills, and tools in education, strengthen the connection between the supply chain and academia, and enhance interdisciplinary collaboration to drive the fashion and textile industry towards greater sustainability and circularity. Originality/Value: This study contributed to the literature by collecting and synthesizing existing research findings. It demonstrated the value and relevance of the research by guiding academic and supply chain cooperation and enhancing interdisciplinary integration with the SDGs.
Keywords: Environmental Sustainability in Business